HISBAH: LEMBAGA KEAMANAN HUKUM DAN PERADILAN - Kamsi, Kamsi (UIN Sunan Kalijaga Yogyakarta, 2012)
Hisbah is an important way of monitoring is known by the Muslims in the early days of Islam that completes supervision to correct and prevent ethical lapses. Hisbah during Umar have an important role in market surveillance and the activities carried out in them, which is ekonomi. This article is aimed at the most important things that exist in the economy by Umar jurisprudence on hisbah and its role in overseeing economic activities. Hisbah is in etimolgy and terminology revolves around the ordering good and forbidding the evil (amar ma’ruf nahi munkar). Terminological meaning hisbah was ordered to leave if there is goodness and forbid unjust if there are practiced. The concept of hisbah above extends to cover all members of society capable of ordering the good and forbidding the evil, whether they are assigned by the state or did not required by resmi. Sebagaimana space hisbah scope includes the rights of Allah and the rights of man. This means that hisbah cover all facets of life. Where is the discussion here will be narrowed explanation hisbah implementation by the state at the time of Umar in matters related to the economy